Socially learned habituation to human observers in wild chimpanzees - Samuni, Liran; Mundry, Roger; Terkel, Joseph; Zuberbühler, Klaus; Hobaiter, Catherine (My University, 2014)
Habituation to human observers is an essential tool in animal behaviour research. Habituation occurs when repeated and inconsequential exposure to a human observer gradually reduces an animal's natural aversive response. Despite the importance of habituation, little is known about the psychological mechanisms facilitating it in wild animals. Although animal learning theory offers some account, the patterns are more complex in natural than in laboratory settings, especially in large social groups in which individual experiences vary and individuals influence each other. Here, we investigate the role of social learning during the habituation process of a wild chimpanzee group, the Waibira community of Budongo Forest, Uganda. Through post hoc hypothesis testing, we found that the immigration of two well-habituated, young females from the neighbouring Sonso community had a significant effect on the behaviour of non-habituated Waibira individuals towards human observers, suggesting that habituation is partially acquired via social learning.